علم سماجیات اور مطالعہ مذہب: نقد و نظر: SOCIOLOGY AND THE STUDY OF RELIGION: A CRITICAL ASSESSMENT (Zia e Tahqeeq, 2025)
Sociologists’ ideas about the causes and consequences of religion are scattered in a variety of studies, each of which focuses on a particular development in the relation of religion to social systems. The resulting literature thus generates a number of claims that appear to be competing and sometimes contradictory. This article mainly focuses on three major schools of thought within sociology and ideas presented by western sociologists about the social role of religion. The study reveals that, despite of their academic contribution in the field, the assumptions made by western sociologists and methods applied to the study of religion are facing serious academic challenges. They are partial and limited in their findings, particularly in their studies on Islam and Muslim societies.